Orchestration of End-to-End Network Services in the 5G-Crosshaul Multi-Domain Multi-Technology Transport Network - Baranda, Jorge; Mangues-Bafalluy, Josep; De la Cruz, Juan Luis; Casellas, Ramon; Vilalta, Ricard; Salvat, Josep X.; Turyagyenda, Charles (IEEE Communications Magazine, 2018)
Upcoming 5G mobile networks are addressing ambitious KPIs not just in terms of capacity and latency, but also in terms of network control and management. In this direction, network management schemes need to evolve to provide the required flexibility, and automated and integrated management of 5G networks. This also applies to the 5G-Crosshaul transport network, which provides an integrated fronthaul and backhaul. Software defined networking and NFV are seen as key enablers for that. This article validates the flexibility, scalability, and recovery capabilities of the 5G-Crosshaul architecture in a testbed distributed geographically. More specifically, the central component of the validation is the hierarchical 5G-XCI, conceived to handle multi-domain multi-technology transport network resources. Its performance is characterized through two experimental case studies. The first one illustrates the automated provisioning of all network resources required to deploy a complete LTE virtual mobile network featuring fronthaul and backhaul configurations. This takes 10.467 s on average for the network under test. The second one exploits the flexibility of the hierarchical XCI to apply local or centralized service recovery in the event of link failure depending on the desired path optimality vs. recovery time trade-off. On average, recovery takes 0.299 s and 6.652 s, respectively. Overall, the proposed solution contributes to attaining the target set for 5G networks of reducing service setup from hours to minutes.
Keywords: Multi-Technology Transport Network; 5G-Crosshaul; Orchestration; End-to-End Network Services